Lentiviral Gag assembly analyzed through the functional characterization of chimeric simian immunodeficiency viruses expressing different domains of the feline immunodeficiency virus capsid protein e114299 - Esteva, Maria Jimena (2014)
To gain insight into the functional relationship between the capsid (CA) domains of the Gag polyproteins of simian and feline immunodeficiency viruses (SIV and FIV, respectively), we constructed chimeric SIVs in which the CA-coding region was partially or totally replaced by the equivalent region of the FIV CA. The phenotypic characterization of the chimeras allowed us to group them into three categories: the chimeric viruses that, while being assembly-competent, exhibit a virion-associated unstable FIV CA; a second group represented only by the chimeric SIV carrying the N-terminal domain (NTD) of the FIV CA which proved to be assembly-defective; and a third group constituted by the chimeric viruses that produce virions exhibiting a mature and stable FIV CA protein, and which incorporate the envelope glycoprotein and contain wild-type levels of viral genome RNA and reverse transcriptase. Further analysis of the latter group of chimeric SIVs demonstrated that they are non-infectious due to a post-entry impairment, such as uncoating of the viral core, reverse transcription or nuclear import of the preintegration complex. Furthermore, we show here that the carboxylterminus domain (CTD) of the FIV CA has an intrinsic ability to dimerize in vitro and form high-molecular-weight oligomers, which, together with our finding that the FIV CA-CTD is sufficient to confer assembly competence to the resulting chimeric SIV Gag polyprotein, provides evidence that the CA-CTD exhibits more functional plasticity than the CA-NTD. Taken together, our results provide relevant information on the biological relationship between the CA proteins of primate and nonprimate lentiviruses.